2016
DOI: 10.1109/comst.2014.2364312
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Survey of the Power Saving Potential in IP-Over-WDM Backbone Networks

Abstract: Abstract-The power consumption in Information and Communication Technologies (ICT) networks is growing year by year; this growth presents challenges from a technical, economic and environmental point of view. This has lead to a great number of research publications on 'green' telecommunication networks. In response, a number of survey works have appeared as well. However, with respect to backbone networks most survey works (a) do not allow for an easy cross-validation of the savings reported in the various wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…With respect to the communication networks footprint for instance, large savings can be obtained by making careful use of wireless networks (since they are inherently less power efficient than wired networks), by introducing sleep modes during off-peak hours, by building equipment with power consumption more proportional to the load, by avoiding large power losses due to equipment doubling for recovery reasons, etc. [9]. Next to these initiatives, further research on Green ICT in industry and academics will be crucial.…”
Section: How To Lower the Internet's Footprintmentioning
confidence: 99%
“…With respect to the communication networks footprint for instance, large savings can be obtained by making careful use of wireless networks (since they are inherently less power efficient than wired networks), by introducing sleep modes during off-peak hours, by building equipment with power consumption more proportional to the load, by avoiding large power losses due to equipment doubling for recovery reasons, etc. [9]. Next to these initiatives, further research on Green ICT in industry and academics will be crucial.…”
Section: How To Lower the Internet's Footprintmentioning
confidence: 99%
“…For instance, an in-depth recent study of energy usage is given in Van Heddeghem et al (2015), where a very simple rule-of-thumb for energy usage is proposed as a universal value for the electrical and optical layers; simplified models of energy usage for various layers and techniques for connections characterized with the number of hops, recovery or its absence, etc., are presented; it is shown that energy efficiency is obtained by reducing marginal energy usage per unit capacity of a card port (a typical decreasing return to scale effect), thus justifying using concave energy profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The SM constitutes a promising alternative to save energy, and consequently to reduce the Electricity Costs (EC) paid by an operator [8,9]. The topic of managing the energy consumption of a core network during its operation has been deeply investigated by different works (see e.g., [10][11][12] for comprehensive surveys).…”
Section: Introductionmentioning
confidence: 99%